2009
DOI: 10.1007/s00049-009-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins in Daphnia detected using commercial antibodies: description and responsiveness to thermal stress

Abstract: It has previously been shown that the level of Daphnia proteins detected by commonly used anti-HSP antibodies, with molecular weights corresponding to those of heat shock proteins, can be modified by various kinds of stress, including the threat of predation. In this study, we demonstrate for the first time that these proteins change their expression in response to thermal stress. Thus, it is concluded that Daphnia heat shock proteins, as components of the cellular stress defense, are involved in both, abiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Interestingly, previous work by Mikulski et al . [ 27 ] has shown that in response to thermal stress, a single clone of D. magna exhibited differential expression of isoforms of hsp70, with upregulation of the 73 and 74 kDa proteins, and inhibition of the 79 kDa protein. Whether such a response varies among genotypes/clones of Daphnia remains an open question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, previous work by Mikulski et al . [ 27 ] has shown that in response to thermal stress, a single clone of D. magna exhibited differential expression of isoforms of hsp70, with upregulation of the 73 and 74 kDa proteins, and inhibition of the 79 kDa protein. Whether such a response varies among genotypes/clones of Daphnia remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…predation [ 26 ]) and abiotic (i.e. temperature [ 27 ]) stressors. These stressors have the potential for causing significant impacts (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To validate blotting and verify equal protein amounts in the lanes [ 18 , 75 ], proteins on the membrane were stained with 0.2% Ponceau S in 1% acetic acid. After blocking the membrane in saline phosphate buffer containing 5% dried milk, the blot was probed using primary anti-HSP60 (SPA-805, dilution 1:1000; Biotrend) as described in [ 76 ] and subsequently goat anti-rabbit horseradish peroxidase-conjugated secondary antibody solution (A6154, dilution, 1: 10000; Sigma Aldrich, Germany). Detection of the chemiluminescence upon incubation with luminol (final concentration, 1.25 mmol/L) and p-coumaric acid (final concentration, 0.2 mmol/L) was performed by exposure to a photographic film (Amersham Hyperfilm ECL, GE Healthcare, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Induction of HSP70 1A in Daphnia magna after the exposure to diclofenac and dimethyl sulfoxide was described by Haap et al ( 2008 ). Production of HSP 60, 70 and 90 kDa in those crustaceans was also observed during heat stress (Mikulski et al, 2009 ; 2011 ). Our study showed that the induction of HSP70 1A was evident in daphnids subjected to heat stress but which were not treated with ECT.…”
Section: Discussionmentioning
confidence: 91%